Evaluating the connection between mean platelet volume (MPV) and peripheral arterial disease risk: A meta-analysis - Dharmawan, Andronikus; Baskoro, Ari (Heart Science Journal, 2024)
BACKGROUND: Numerous studies have been conducted to evaluate the role of Mean Platelet Volume (MPV) in relation to Peripheral Artery Disease (PAD). However, the results of these studies have been inconsistent regarding the significance of MPV as an indicator for PAD.OBJECTIVE: This meta-analysis aimed to clarify the role of MPV in PAD by collecting and analyzing data from various studies. The goal was to provide a more definitive assessment of whether MPV levels could serve as a reliable indicator for PAD.METHODS: We conducted a meta-analysis from July to August 2024, utilizing data from three major databases: Scopus, Embase, and PubMed. We gathered data on MPV levels from studies comparing PAD patients with control groups. The meta-analysis included cumulative effect estimates, with analysis performed using the inverse variance method to synthesize data and evaluate the overall effect of MPV on PAD.RESULTS: Nine studies were included in this meta-analysis, comprising 1,214 PAD cases and 6,568 controls. Our analysis demonstrated that MPV was a significant marker in PAD, with PAD patients having higher MPV levels compared to controls (MD: 0.46; 95%CI: 0.25, 0.66; p Egger: 0.0911; p Heterogeneity <0.0001; p <0.0001).CONCLUSION: Our findings support that MPV is an important indicator in the context of PAD. Further study is needed to explore the clinical applications of MPV in PAD and to establish standardized thresholds for its use in clinical practice.